Atributos físico-hídricos de um Latossolo após a aplicação de lodo de esgoto em área degradada do Cerrado - Campos, Fabiana da Silva de [UNESP]; Alves, Marlene Cristina [UNESP]; Souza, Zigomar Menezes de; Pereira, Gener Tadeu [UNESP] (Universidade Federal de Santa Maria (UFSM), 2011)
Os solos cultivados intensivamente e inadequadamente são degradados, assim como a construção de obras civis no meio rural executada sem atender à legislação. O trabalho objetivou definir a interferência do lodo de esgoto na recuperação de atributos de um Latossolo Vermelho. O experimento foi implantado em 2004, em Selviria (MS). Os tratamentos utilizados foram: T1-vegetação de cerrado; T2-solo exposto sem tratamento para recuperação; T3-solo cultivado com eucalipto e braquiária sem o uso do lodo de esgoto e adubação mineral; T4-solo cultivado com eucalipto e braquiária com adubação mineral; T5-solo cultivado com eucalipto e braquiária com uso de 30Mg ha-1 de lodo de esgoto e; T6-solo cultivado com eucalipto e braquiária com uso de 60Mg ha-1 de lodo de esgoto. Nas camadas do solo de 0,00-0,05; 0,05-0,10; 0,10-0,20 e de 0,20-0,30m, foram avaliados os atributos físico-hídricos e teor de matéria orgânica. Os tratamentos com adubação mineral e orgânica estão agindo de forma semelhante para a recuperação dos atributos físico-hídricos e do teor de matéria orgânica. em solos degradados pela construção de obras civis a aplicação de 30 a 60mg de lodo de esgoto ha-1 recupera as suas propriedades físico-hídricas.

Intensively and inadequately managed soils and the civil construction industry in the rural area that are unconcerned with specific legislation, result in several problems in the environment. The objective of the present study was to evaluate the influence of sewage sludge on the recovery of hydro-physical properties of an Oxisol. The experiment was implanted in 2004, in Selvíria, Mato Grosso do Sul, Brazil. The six experimental treatments were arranged according to a randomized complete-block design with four replications. The experimental treatments were: 1 - Native Cerrado vegetation; 2 - degraded soil without treatment for soil recovery; 3 - Eucalyptus citriodora planting and Brachiaria decumbens sowing and no sewage sludge or mineral fertilization use; 4 - Eucalyptus citriodora planting and Brachiaria decumbens sowing in soil enriched with mineral fertilizer; 5 - Eucalyptus citriodora planting and Brachiaria decumbens sowing in soil enriched with 30Mg ha-1 sewage sludge, and 6- Eucalyptus citriodora planting and Brachiaria decumbens sowing in soil enriched with 60Mg ha-1 sewage sludge. Hydro-physical properties and the soil organic matter content were characterized at 0.00-to-0.05; 0.05-to-0.10; 0.10-to-0.20 and 0.20-to-0.30m layers in the soil. Mineral and organic fertilization treatments showed similar effects on the recovery of the hydro-physical properties and organic matter content of the degraded soil. The hydro-physical properties and organic matter content of Cerrado soils degraded due to civil construction activities can be recovered by the use of 30 to 60Mg sewage sludge ha-1.
Hydro-physical attributes of an Oxisol after sewage sludge application on a Cerrado degraded area
Keywords: Soil degradation; soil recovery; Eucalyptus; Pasture; organic matter; Solos - Degradação; recuperação do solo; Eucalipto; braquiária; Matéria orgânica do solo